2015
DOI: 10.1371/journal.pone.0120514
|View full text |Cite
|
Sign up to set email alerts
|

A C-Type Lectin from Bothrops jararacussu Venom Disrupts Staphylococcal Biofilms

Abstract: Bovine mastitis is a major threat to animal health and the dairy industry. Staphylococcus aureus is a contagious pathogen that is usually associated with persistent intramammary infections, and biofilm formation is a relevant aspect of the outcome of these infections. Several biological activities have been described for snake venoms, which led us to screen secretions of Bothrops jararacussu for antibiofilm activity against S. aureus NRS155. Crude venom was fractionated by size-exclusion chromatography, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 48 publications
2
26
0
2
Order By: Relevance
“…In this study, the susceptibility of S. aureus to seven snake venoms from the family Viperidae (Bothropoides erythromelas, B. jararaca, B. neuwiedi There are several reports in the literature on the antibacterial activity of snake venom against grampositive and gram-negative bacteria (Lu et al, 2002;Stábeli et al, 2004;Klein et al, 2015), including Bacillus subtilis, Sarcina spp., Escherichia coli and S. aureus. A previous study with B. marajoensis venom (also of the family Viperidae), revealed that it was able to inhibit the growth of P. aeruginosa, S. aureus and Candida albicans, thereby demonstrating an antifungal effect is also present in some venoms (Costa-Torres et al, 2010).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…In this study, the susceptibility of S. aureus to seven snake venoms from the family Viperidae (Bothropoides erythromelas, B. jararaca, B. neuwiedi There are several reports in the literature on the antibacterial activity of snake venom against grampositive and gram-negative bacteria (Lu et al, 2002;Stábeli et al, 2004;Klein et al, 2015), including Bacillus subtilis, Sarcina spp., Escherichia coli and S. aureus. A previous study with B. marajoensis venom (also of the family Viperidae), revealed that it was able to inhibit the growth of P. aeruginosa, S. aureus and Candida albicans, thereby demonstrating an antifungal effect is also present in some venoms (Costa-Torres et al, 2010).…”
Section: Resultsmentioning
confidence: 92%
“…When tested with ½ x MIC, B. moojeni venom was able to inhibit 90% of biofilm formation, without affecting bacterial growth. Recently, Klein et al (2015) demonstrated for the first time that a lectin purified from the venom of Bothrops jararacussu disrupts staphylococcal biofilms. These findings are of interest because nosocomial infections involving the formation of biofilm caused by S. aureus are often difficult to treat with antibiotics.…”
Section: Acta Scientiarum Biological Sciencesmentioning
confidence: 99%
“…; Klein et al . ). A recent study demonstrated the anti‐biofilm activity of a C‐type lectin from Bothrops jararacussu venom on staphylococcal biofilms (Klein et al .…”
Section: Discussionmentioning
confidence: 97%
“…A recent study demonstrated the anti‐biofilm activity of a C‐type lectin from Bothrops jararacussu venom on staphylococcal biofilms (Klein et al . ). According to these authors the lectin could interact with biofilm carbohydrates via carbohydrate‐binding domain, disturbing the biofilm formation during bacterial growth.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation